Community Structure Of Sea Cucumber (Holothuroidea) In The Coastal Area Of The Island Of Jailolo Subdistrict Nyaregilaguramangofa South Halmahera Regency West Of North Maluku - Gajali Husain; Jan W. S. F. Tamanampo; Gaspar D. Manu (Sam Ratulangi University, 2017)
Sea cucumbers (Holothuroidea) are a group of marine invertebrate animals of the class Holothuroidea (phylum Echinodermata). At present, hunting of sea cucumbers is not only targeted at species of high economic value, but also of low economic value. The pressure of exploitation has led to a decline in the population that can cause changes in the structure of the community. The purpose of this research is to understand the type of sea cucumber, analyze the structure of sea cucumber which includes individual density, diversity index, domination index, inter species association and dispersion pattern. Sampling was conducted at night during the lowest tide in April 2016. Based on the results of research conducted in the coastal area of Nyaregilaguramangofa Island, South Jailolo district, West Halmahera Regency, North Maluku. Species of sea cucumbers found in the study sites were 6 species of sea cucumber: Holothuria atra, Holothuria hilla, Holothuria scabra, Bohadschia marmorata, Bohadschia vitiensis and Ophedesoma grisea, each with an average individual density of 0.029 ind/m2, the diversity index (H '= 1,495), the fairness index (e = 0.834), the dominance index (C = 0.260), the association between the six species forming 4 pairs of positive associations and 11 pairs of negative associations and the entire population has a randomly distributed pattern.Keywords: Structure communities, Holothuroidea, Nyaregilaguramangofa, Nort Maluku ABSTRAKTeripang (Holothuroidea) adalah kelompok hewan avertebrata laut dari kelas Holothuroidea (filum Echinodermata). Pada saat ini, perburuan teripang tidak hanya ditargetkan pada spesies yang bernilai ekonomis tinggi, tetapi juga yang bernilai ekonomis rendah. Tekanan eksploitasi telah menyebabkan penurunan populasi yang dapat menyebabkan perubahan pada struktur komunitasnya. Adapun tujuan dari penelitian ini yaitu untuk memahami jenis teripang, menganalisis struktur teripang yang meliputi kepadatan individu, indeks keanekaragaman, indeks dominasi, asosiasi antar spesies dan pola penyebaran. Pengambilan sampel dilakukan pada malam hari saat surut terendah pada bulan April 2016. Berdasarkan hasil penelitian dilakukan di kawasan pantai Pulau Nyaregilaguramangofa, kec. Jailolo Selatan Kab. Halmahera Barat, Maluku Utara. Spesies teripang yang ditemukan di lokasi penelitian berjumlah 6 spesies teripang: Holothuria atra, Holothuria hilla, Holothuria scabra, Bohadschia marmorata, Bohadschia vitiensis dan Ophedesoma grisea, masing-masing dengan kepadatan individu rata-rata 0.029 ind/m, indeks keanekaragaman (H' = 1.495), indeks kemerataan atau keserasian (e = 0.834), indeks dominansi (C = 0.260), asosiasi antar 6 spesies membentuk 4 pasang asosiasi positif dan 11 pasang asosiasi negatif dan keseluruhan populasi memiliki pola penyebaran secara acak.Kata kunci : Struktur komunitas, teripang, Nyaregilaguramangofa, Maluku Utara